(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Gli edifici di culto come testimonianze di tradizioni religiose e culturali - 2. Peculiarità degli edifici di culto delle chiese ortodosse - 3. Il patrimonio storico e culturale greco-ortodosso - 4. La presenza delle comunità russofone - 5. Le altre circoscrizioni ecclesiastiche. La diocesi romena d’Italia. Le Comunità serba e bulgara - 6. Rilevanza della cultura armena. Orthodox buildings of worship in Italy as testimonies of the faith, memories and culture of peoples ABSTRACT: The buildings of worship testify and recall religious and cultural traditions of citizens-faithful, even when they are places of worship of the Eastern Churches, in species pertaining to the Greek Orthodox or Russian Orthodox cult, long present and officiated in Italy. The role of buildings already used for Roman Catholic worship and now given, in various capacities, to other Eastern Orthodox Churches is different. The centuries-old presence of Armenian culture in some areas of Italy is worth mentioning.